Pembinaan Peran Manajemen Keuangan Digital dalam Pengelolaan Keuangan pada UMKM - Hikmah Hikmah; Dian Efriyenti; Risca Azmiana (Yayasan Literasi Sains Indonesia, 2026)
This community service activity focuses on strengthening the role of digital financial management in managing finances among MSME actors. Financial management in MSMEs heavily depends on the implementation of digital financial systems, which enable business actors to optimize efficiency, improve accuracy, manage cash flow and inventory, and obtain relevant financial information for decision-making. However, various challenges have hindered significant improvements in MSME performance, particularly limited understanding of financial planning and management, as well as low levels of digital literacy. MSMEs in Barelang Mega Jaya Sejati Housing are predominantly engaged in the culinary and fashion sectors, with the main issue being a lack of familiarity with digital financial applications. The implementation method consisted of training, mentoring, and periodic evaluations at the end of each session to identify obstacles and determine necessary follow-up actions. The results indicate an improvement in participants’ understanding and skills in recording and preparing simple financial reports using digital applications. This activity has contributed positively to enhancing digital financial literacy and promoting household economic independence. Practically, this program demonstrates that a hands-on mentoring-based training approach using simple digital applications can serve as an effective model to improve MSME financial management capacity. This community service model also offers novelty through the integration of financial literacy and digital literacy simultaneously and has the potential to be replicated in other MSME communities with similar characteristics by adjusting to their level of digital literacy and business types.